Development of Students' Spiritual Intelligence at MTs Esa Nusa Islamic School - Ahmad Buchori Muslim; M. Syarif Alrafisyah; Salma Aulia Azizah; Shafira Zahra (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
Education is a process to mature humans and humanize humans. Through education, humans can grow and develop naturally and perfectly. So, he can carry out his duties as a human. This study aims to determine the application of spiritual intelligence in education. This research is a qualitative study that uses the collection of some data. The data collection used in this research uses observation and interviews as its sources. In analyzing the data, researchers can see how effective the application of spiritual intelligence is for students in education. The results of this study indicate that in the application of spiritual intelligence, a teacher and parents have an important role in developing students' spiritual intelligence. Building a good relationship between teachers, parents and schools is also one of the supporters of the development of spiritual intelligence through various programs that can be applied to students. In its application, there must also be several factors and challenges for teachers and parents that come from both internal and external sources. The results of the research that have been obtained are expected to be able to be taken into consideration in the application of spiritual intelligence and become a reference for future research.